Pemberdayaan Masyarakat melalui Pemanfaatan Sampah Organik Rumah Tangga sebagai Pupuk Organik Cair (POC) untuk Mendukung Ketahanan Pangan Skala Rumah Tangga di RW 13 Giwangan, Yogyakarta - Devi Oktaviana Latif; Fachrudin Abdul Rozaq (Direktorat Pengabdian kepada Masyarakat, 2026)
Household organic waste remains a major environmental challenge in urban residential areas, particularly in densely populated neighborhoods with limited land availability. Most organic waste has not been properly managed and is still disposed of in landfills, leading to potential environmental pollution. At the same time, household-level food security has become an increasingly important issue, especially for urban communities with limited access to productive land. This community service activity aimed to enhance public awareness and understanding of the utilization of household organic waste as liquid organic fertilizer (LOF) as an initial effort to support household food security and sustainable environmental management. The activity was conducted in RW 13 Giwangan, Umbulharjo District, Yogyakarta City, targeting a group of male residents. The implementation method employed a community-based educational approach through socialization sessions and the dissemination of visual information media in the form of posters. The socialization covered basic concepts of organic waste classification, the principles of LOF production, and its potential use for home gardening. Educational posters were installed on the neighborhood notice boards to reinforce key messages and provide continuous access to information for the wider community. The results indicate that socialization activities combined with visual media effectively improved residents’ understanding of the potential value of household organic waste and alternative waste management practices. Although no hands-on training was conducted, the increase in environmental literacy represents an important initial achievement in fostering attitude and behavior change. Furthermore, the activity introduced residents to the linkage between organic waste management and household food security through the utilization of limited residential spaces. Overall, this community service activity contributes to building environmental awareness and community readiness toward more sustainable household waste management practices.